Screw extrusion-based additive manufacturing of PEEK. (15th February 2018) - Tseng, Jian-Wei; Liu, Chao-Yuan; Yen, Yi-Kuang; Belkner, Johannes; Bremicker, Tobias; Liu, Bernard Haochih; Sun, Ta-Ju; Wang, An-Bang
Abstract: Polyether-ether-ketone (PEEK) has high mechanical strength, thermal performance, and biocompatibility, and is widely used in biomedical and chemical engineering applications. However, to date there are no guidelines for the building of a 3D printer for highly viscous materials, e.g., PEEK. In this paper, a screw extrusion method was developed to overcome the existing problems of the filament-feeding method. Excellent flow stability (< 3% variation) and high printing speed (up to 370 mm/s) for PEEK printing were achieved. Highly reproducible mechanical tests of the printing products were demonstrated with 96% of the bulk material strength for the first time. Furthermore, an exchangeable printing head was built to cover both line- and plane-printing needs to widen its applications and improve printing surface quality (up to 0.945 nm in Ra). All printed material had a more brittle character in comparison with the bulk material and the post annealing process was found to have no significant effect on the mechanical strength. Additionally, porous artificial intervertebral cages with controllable size and distribution were manufactured to demonstrate potential applications. Graphical abstract: Image 1 Highlights: A new screw extrusion-based 3D printing system was designed to solve the problems of conventional filament feeding ones. High viscosity and melting temperature material e.g., polyether-ether-ketone (PEEK), has been printed with good quality. Stable flow ability (<3% variation) with high printing speed (up to 370 mm/s) and reproducible quality was demonstrated. 96% of the mechanical strength of the bulk material (PEEK) in additive manufacturing printing was achieved. SEM and XRD results revealed the thermal condition was the major factor affecting mechanical strength. The post annealing process had no significant effect on the material properties.